The Influence of Inclusive Hiring Policies on Workplace Culture is Evident in Puntland’s Public and Private Sectors - Shire, Ubah Mohamed (International Journal of Scientific Research and Management (IJSRM), 2025)
The impact of inclusive hiring practices on workplace culture in Puntland's public and private sectors is examined in this study. In order to promote an equal workplace, Puntland's institutions have started using inclusive recruitment practices as businesses around the world place a higher priority on diversity and equity. The research emphasizes the formation of cooperation, respect, and innovation among increasingly diverse teams, highlighting the significant change in workplace dynamics. The results of an analysis of how these rules affect employee diversity, corporate culture, and general employee happiness show that inclusive recruiting improves social cohesiveness in the area in addition to improving organizational performance. The study highlights the promise of inclusive hiring as a strategic workforce development method, despite ongoing hurdles like structural barriers and deeply ingrained cultural norms. According to the findings, removing these barriers is crucial to creating inclusive workplaces where all workers may succeed and improve Puntland's socioeconomic situation.